A Host‐Configured Lithium–Sulfur Cell Built on 3D Nickel Photonic Crystal with Superior Electrochemical Performances. Issue 21 (18th April 2018) - Lin, Shengxuan; Yan, Yang; Cai, Zihe; Liu, Lin; Hu, Xiaobin
Abstract: The insulator of the sulfur cathode and the easy dendrites growth of the lithium anode are the main barriers for lithium–sulfur cells in commercial application. Here, a 3D NPC@S/3D NPC@Li full cell is reported based on 3D hierarchical and continuously porous nickel photonic crystal (NPC) to solve the problems of sulfur cathode and lithium anode at the same time. In this case, the 3D NPC@S cathode can not only offer a fast transfer of electron and lithium ion, but also effectively prevent the dissolution of polysulfides and the tremendous volume change during cycling, and the 3D NPC@Li anode can efficiently inhibit the growth of lithium dendrites and volume expansion, too. As a result, the cell exhibits a high reversible capacity of 1383 mAh g −1 at 0.5 C (the current density of 837 mA g −1 ), superior rate ability (the reversible capacity of 735 mAh g −1 at the extremely high current density of 16 750 mA g −1 ) with excellent coulombic efficiency of about 100% and an excellent cycle life over 500 cycles with only about 0.026% capacity loss per cycle. Abstract : A lithium–sulfur cell built on 3D hierarchical and continuous porous nickel photonic crystal easily solves the problems of sulfur cathode (nonconductivity of sulfur, dissolution of polysulfides, and volume change) and lithium metal anode (lithium dendrites growth and volume expansion) simultaneously.